Diffraction-based acoustic manipulation in microchannels enables continuous particle and bacteria focusing. Issue 15 (1st July 2020) - Devendran, Citsabehsan; Choi, Kyungyong; Han, Jongyoon; Ai, Ye; Neild, Adrian; Collins, David J.
Abstract : We explore a unique diffractive acoustic phenomenon arising from a surface acoustic wave and channel elements, which we term diffractive acoustic surface acoustic waves (DASAW), which can be applied robustly for all channel orientations. Abstract : Acoustic fields have shown wide utility for micromanipulation, though their implementation in microfluidic devices often requires accurate alignment or highly precise channel dimensions, including in typical standing surface acoustic wave (SSAW) devices and resonant channels. In this work we investigate an approach that permits continuous microscale focusing based on diffractive acoustics, a phenomenon where a time-averaged spatially varying acoustic pressure landscape is produced by bounding a surface acoustic wave (SAW) transducer with a microchannel. By virtue of diffractive effects, this acoustic field is formed with the application of only a single travelling wave. As the field is dictated by the interplay between a propagating substrate-bound wave and a channel geometry, the pressure distribution will be identical for a given channel orientation regardless of its translation on a SAW substrate, and where small variations in channel size have no substantive effect on the pressure field magnitude or overall particle migration. Moreover, in the case of a channel with dimensions on the order of the diffractive fringe pattern spacing, the number of focusing positions will be identical for all channel orientations, with acoustic radiation forces pushing suspended particles to the channel edges. We explore this highly robust particle manipulation technique, determining two distinct sets of streaming and acoustic radiation dominant concentration positions, and show the continuous focusing of polystyrene 1 μm and 0.5 μm diameter particles and fluorescently labeled E. coli bacteria cells at flow rates exceeding those of previous microfluidic implementations for micron and submicron sized particles.